Relasi Game Warspear dan Kemampuan Berbicara Serta Kosakata Mahasiswa Sastra Inggris Universitas Ngudi Waluyo - Deswandito Dwi Saptanto; Tri Arie Wibowo (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2018)
The material and learning process in lectures to improve speaking skills and vocabulary at present generally still have a conventional pattern that is with the teaching and learning process such as lectures, giving material or topics to be discussed along with role play activities as well as structured assignments with media practice questions. Students who have received lecture materials with conventional methods tend to have a sense of boredom, this will certainly lead to a decline in the level of enthusiasm of student learning, as well as directly impacting the existence and presence of students in the lectures. Creative, innovative and interactive learning processes become problem solvers of this problem. This study contributes that is combining between giving lecture material creatively and innovatively by using information and communication technology media in the form of games in order to improve the ability and enthusiasm of students to learn speech and vocabulary material interactively. In this study, researchers used a game called Warspear which focused on communication that occurred between characters in the game. This study uses a qualitative descriptive method in the form of surveys, giving questionnaires, interviews and observations. The method is to answer the problem that the game can improve the ability of students in the scope of speaking and vocabulary and games are good learning tools, and have a positive impact on students.